2010
DOI: 10.3109/00016481003629036
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin in the treatment of acute bacterial rhinosinusitis: Results of a multicenter, non-interventional study

Abstract: In all, 578 patients with ABS treated with moxifloxacin were valid for effectiveness analysis. An improvement was observed in 98.8% (n = 571/578) of the patients. Cure was documented in 89.4% (n = 517/578) of the patients. The physicians' overall tolerability rating was 'very good' or 'good' in 92.9% (n = 537/578) of patients. The incidence rates of AEs and ADRs were 1.5% (n = 10/681) and 0.6% (n = 4/681), respectively. No serious AE was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Many clinical studies have shown the efficacy of moxifloxacin in the treatment of acute maxillary sinusitis (Arrieta et al, 2007;Gehanno et al, 2003;Johnson et al, 2008;Rakkar et al, 2001;Zhou et al, 2010). In our opinion, the microbiological results of this study suggest that clinical trials should be designed to investigate the clinical usefulness of moxifloxacin in the treatment of chronic maxillary sinusitis also.…”
Section: Discussionmentioning
confidence: 91%
“…Many clinical studies have shown the efficacy of moxifloxacin in the treatment of acute maxillary sinusitis (Arrieta et al, 2007;Gehanno et al, 2003;Johnson et al, 2008;Rakkar et al, 2001;Zhou et al, 2010). In our opinion, the microbiological results of this study suggest that clinical trials should be designed to investigate the clinical usefulness of moxifloxacin in the treatment of chronic maxillary sinusitis also.…”
Section: Discussionmentioning
confidence: 91%
“…[37,40] These data did not show significantly higher toxicity of moxifloxacin compared with commonly used antibiotics if the contraindications and precautions of use mentioned in the Summary of Product Characteristics[41–43] are taken into account. Post-marketing studies[4453] have confirmed that moxifloxacin is generally well tolerated in medical practice, without new or unanticipated serious adverse events (SAEs) beyond those already established from controlled clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that moxifloxacin treatment of acute bacterial rhinosinusitis produces rapid symptom improvement with good tolerability [25], [26], and is at least effective as comparator antibiotics [32][35]. Numerous variables may affect the relevance of the results from randomised controlled trials to everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic and antibacterial characteristics of moxifloxacin support its use in acute bacterial rhinosinusitis [22], [24] and previous studies have shown that treatment with moxifloxacin rapidly improves the signs and symptoms of affected patients [25], [26]. According to several clinical guidelines, this respiratory fluoroquinolone is an appropriate choice of antibiotic in selected cases, such as those with more severe disease, those with a history of β-lactam allergy, where first-line antibiotic treatment has failed, where resistance to first-line antibiotics is suspected or in patients for whom the consequences of treatment failure could be serious [9], [10], [27].…”
Section: Introductionmentioning
confidence: 91%